Hubungan Tingkat Pengetahuan dengan Perilaku Ibu dalam Upaya Pencegahan Stunting pada Anak Usia 6-24 Bulan - Muncan, I Gusti Agung Mas Widia Paramitha; Sriasih, Ni Kadek; Rismawan, Made (Jurnal Gema Keperawatan, 2025)
Efforts to prevent stunting in children aged 6-24 months are supported by knowledge and behavior of mothers, however, in reality, many mothers are found to have poor knowledge about and behavior in stunting prevention. This study employed an analytic design and cross-sectional study approach and took place in the working area of Public Health Centre I West Denpasar in April 2024. The sample was 230 respondents, selected through purposive sampling technique. The data were collected using a questionnaire and analyzed using the Spearman-Rho correlation statistical test. This study has been ethically approved by the ethics commission of ITEKES Bali. The results of this study showed that all respondents (100%) had a good knowledge and good behavior in stunting prevention. The correlation test revealed a significant correlation between the level of knowledge and behavior of mothers in stunting prevention p-value 0,001 with a value of r 0,269. The better the mother's knowledge, the better the mother's behavior. Subsequent research should explore further about behavior of mothers in stunting prevention.